EFEK ILMU BEBAS NILAI DAN RELEVANSINYA TERHADAP PENGEMBANGAN SENJATA NUKLIR DI DUNIA (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2023)
This study examines the impact of value-free science on the development of nuclear weapons by several developed countries. The aim is to understand the reasons and motives behind these countries' pursuit of nuclear weapons. The production of nuclear weapons by these countries has reached a significant level, indicating underlying factors that drive their competition. The methodology employed in this study is a literature review. By examining the effects of value-free science, particularly in relation to the development of nuclear weapons, information was gathered from various sources. The study reveals that the production and proliferation of nuclear weapons by several developed countries for military purposes can be attributed to the influence of value-free science. In this context, value-free science implies that these countries have prioritized their own interests over social welfare.
Keywords: value-free; science; nuclear; human development